Influence of programmed death ligand 1 (PD-L1) knockout on gut microbiota in experimental autoimmune uveitis - Gu, Junxiang; Ma, Yixian; Chang, Qing; Chen, Ling (Frontiers in Immunology, 2025)
PurposeProgrammed death ligand 1 (PD-L1) is a potential target for autoimmune disease therapies. The gut microbiota plays a critical role in autoimmunity, and may influence therapeutic outcomes of immune therapies in cancer. However, the relationship between PD-L1 and gut microbiota in autoimmune conditions remains unclear. This study aims to investigate the effect of PD-L1 knockout on gut microbiota in an experimental autoimmune uveitis (EAU) model.MethodsEAU was induced via immunization with interphotoreceptor retinoid-binding protein peptide 651-670 (IRBP651-670) in either wild type (WT) or PD-L1 knockout (KO) C57BL/6J female mice. Sham adjuvant was administered to WT or PD-L1 KO mice as healthy controls. The severity of EAU was evaluated through clinical evaluation and histopathological gradings. The characteristics of gut microbiota was analyzed using metagenomic sequencing.ResultsEach group consisted of three biological replicates. The clinical and histopathological scores of EAU were significantly higher in KO_EAU mice than in WT_EAU mice. WT_EAU mice exhibited lower microbial richness than their healthy controls (WT mice), while PD-L1 KO in EAU mice (KO_EAU group) led to increased richness when compared to wild type EAU mice (WT_EAU group). EAU induced a reduction in the abundance of Akkermansia muciniphila A and an increased in CAG-485 sp002362485. PD-L1 knockout in EAU led to an increased abundance of families Bacteroidaceae, Lachnospiraceae and Ruminococcaceae. EAU was associated with declining microbial tryptophan metabolism and up-regulated functions related to lipid and carbohydrate metabolism; PD-L1 knockout in EAU further increased the metabolism of glycan and biosynthesis of 3-deoxy-α-D-manno-2-octulosonate (Kdo), a key component of bacterial lipopolysaccharide (LPS).ConclusionBoth EAU and PD-L1 knockout modulate gut microbiota, affecting microbial composition - particularly Akkermansia, CAG-485, Bacteroidaceae, Lachnospiraceae and Ruminococcaceae - and microbial functions such as lipid, carbohydrate and glycan metabolism.